Coenzyme Q10 supplementation in burn patients: a double-blind placebo-controlled randomized clinical trial - Zahra Kiani; Nadereh Khorsand; Fahimeh Beigi; Gholamreza Askari; Manoj Sharma; Mohammad Bagherniya (Trials, 2024)
Abstract Background Burn injuries are important medical problems that, aside from skin damage, cause a systemic response including inflammation, oxidative stress, endocrine disorders, immune response, and hypermetabolic and catabolic responses which affect all the organs in the body. The aim of this study was to determine the effect of coenzyme Q10 (CoQ10) supplementation on inflammation, oxidative stress, and clinical outcomes in burn patients. Methods In a double-blind placebo-controlled randomized clinical trial, 60 burn patients were randomly assigned to receive 100 mg CoQ10 three times a day (total 300 mg/day) or a placebo for 10 days. Inflammatory markers including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), oxidative stress markers including total antioxidant capacity (TAC), malondialdehyde (MDA) and superoxide dismutase (SOD) activity, fasting blood glucose (FBG), blood urea nitrogen (BUN), creatinine, white blood cells (WBC), and body temperature were assessed as primary outcomes and albumin, prothrombin time (PT), partial thromboplastin time (PTT), international normalized ratio (INR), other hematological parameters, blood pressure, O2 saturation, ICU duration, and 28-mortality rate were assessed as secondary outcomes. Results Fifty-two participants completed the trial. CRP and ESR levels were not significantly different between CoQ10 and placebo groups at the end of the study (P = 0.550 and P = 0.306, respectively). No significant differences between groups were observed for TAC (P = 0.865), MDA (P = 0.692), and SOD activity (P = 0.633) as well. Administration of CoQ10 resulted in a significant increase in albumin levels compared to placebo (P = 0.031). There was no statistically significant difference between the two groups in other measured outcomes (P > 0.05). Conclusion Results showed that in patients with burn injury, CoQ10 administration had no effect on inflammatory markers and oxidative stress, although serum albumin levels were improved after supplementation. Further studies with albumin as the primary outcome are needed to confirm this finding.